Normal variation of bone marrow B‐cell precursors according to age – reference ranges for studies in myelodysplastic syndromes in Brazil. Issue 5 (14th December 2017) - Lorand‐Metze, I.; Longhini, A. L.; Oliveira‐Duarte, G.; Correia, R. P.; Santos‐Silva, M. C.; Yamamoto, M.; Sandes, A. F.; Oliveira, A. F.; Souto, E. X.; Ikoma, M. R. V.; Pereira‐Cunha, F. G.; Beltrame, M.; et al.
Abstract : Background: Normal B lymphoid maturation occurs in bone marrow (BM) throughout life, but immature B‐cell progenitors (BCPs) are more numerous in children than in adults. To assess the normal values according to age became important as BCPs are decreased in myelodysplastic syndromes and have been considered an important diagnostic and prognostic feature in these clonal disorders. Methods: in a multicenter retrospective study from the Brazilian Group of Flow Cytometry we analyzed the variation of BCPs in normal BM according to age and technical peculiarities of each laboratory. We analysed of 45 BM donors and 89 cases examined for elucidation of transitory reactive cytopenias presenting a normal BM immunophenotyping. BCPs were enumerated as CD19 + /CD34 + /CD45 dim /CD10 + cells (panel 1) or CD19 + /CD34 + /CD45 dim cells (panel 2) among the total nucleated non‐erythroid cells and as percentage of CD34 + cells. Results: we included 134 cases. Panel 1 was applied in 88 cases and panel 2 was used in 46. Age range: 10 months to 89 years. In a multiple regression, % BCPs/total nucleated cells was an exponential function of age. Age explained alone 49.4% of the variance, while 'panel used' explained 1.8% and 'laboratory' explained 0.7%. Age explained only 24.9% of the variance of BCPs/CD34 + cells. Conclusions: in normal individuals, BM B‐cell precursors varied mainly according to age, but were also dependent on technical peculiarities of operators and equipments. Analysis by phenotype and as percentage of total nucleated cells was more accurate and less susceptible to variation than evaluating % BCPs/total CD34 + cells. © 2017 International Clinical Cytometry Society